(untitled) (Journal of the College of Education for Women, 2018)
All modern critical approaches attempt to cover the meanings and overtones of the text, claiming that they are better than others in the analysis and attainment of the intended meanings of the text. The structural approach claims to be able to do so more than any other modern critical approach, as it claimed that it is possible to separate what is read from the reader, on the presumed belief that it is possible to read the text with a zero-memory. However, the studies in criticism of criticism state that each of these approaches is successful in dealing with the text in one or more aspects while failing in one or more aspects. Consequently, the criticism whether the approach possesses the text, or that the text rejects this possession, remains in search for its completion in different approaches. Therefore, the rivalry between modern critical approaches remained in order to avoid incomplete coverage of the text. But, can the complete coverage of the text be achieved? This question remains, in its essence, a philosophical one. Therefore, can we find an objective answer for it? Keywords: Structuralism, Text, Critical approaches, Structural approach